Chlorophytum bharuchae Ansari, Raghavan et Hemadri - a New Species of Liliaceae from Western Ghats - Ansari, M. Y.; Raghavan, R. S.; Hemadri, K. (Indian Forester, 1970)
Chlorophytum bharuchae Ansari, Raghavan et Hemadri sp. nov. collected from Western Ghats of Maharashtra and Mysore States is described with illustrations.